Mahasiswa, Obat-obatan, dan Prilaku Kesehatan (Studi Perilaku Pengobatan Mandiri Mahasiswa Universitas Negeri Semarang dalam Mengonsumsi Obat) - Farika Tri Ariyanti; Fadly Husain; Asma Luthfi (SOSIO EDUKASI Jurnal Studi Masyarakat dan Pendidikan, 2018)
The indication of risky health behavior in students can lead into a disease. Self-medication is the most common form of therapy chosen by someone who relies on medication distribution as pharmacy does. As for choosing the medicines, it requires adequate knowledge to adjust between the types of disease and the types of medicines. Qualitative method is used in this research using observation, interview, and documentation as the collected data. The results are: (1) the diseases suffered by Unnes students according to their risky health behavior are maag, diarhea, headache, scabies, and influenza. (2) Unnes studentâ€™s risky health behavior are the irregular eating pattern, unbalanced nutrition, less rest time, and less exercises. (3) Unnes students prefer to take self-medication in overcoming the suffered disease using pharmacy, store, or stall medicines until the reuse of prescription. Keywords:  Illness behavior, risky health behavior, self medication.